2018
DOI: 10.1021/acsaem.8b01139
|View full text |Cite
|
Sign up to set email alerts
|

Ta2O5 Coating as an HF Barrier for Improving the Electrochemical Cycling Performance of High-Voltage Spinel LiNi0.5Mn1.5O4 at Elevated Temperatures

Abstract: The high-voltage spinel LiNi 0.5 Mn 1.5 O 4 cathode material suffers from the rapid degradation of electrochemical cycling performance at elevated temperatures, which prevents its successful commercialization. Herein, we show that coating the surface of this material with Ta 2 O 5 , which has high resistance against hydrofluoric acid (HF) attack, is an effective way to improve its electrochemical cycling performance. A Ta 2 O 5 -coated LiNi 0.5 Mn 1.5 O 4 half-cell shows a capacity retention of ∼93% and a Coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 81 publications
3
42
0
Order By: Relevance
“…In Figure 8b there is a clear Ti peak that is not visible in the LNMO spectrum. The TiO 2 ‐coating has been reported to be offering only temporary protection from HF attack, as it will be fluorinated [41] . Furthermore, Cheng et al [33] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Figure 8b there is a clear Ti peak that is not visible in the LNMO spectrum. The TiO 2 ‐coating has been reported to be offering only temporary protection from HF attack, as it will be fluorinated [41] . Furthermore, Cheng et al [33] .…”
Section: Resultsmentioning
confidence: 99%
“…The TiO 2coating has been reported to be offering only temporary protection from HF attack, as it will be fluorinated. [41] Furthermore, Cheng et al [33] reported that the TiO 2 -coating they deposited by ALD on an LCO electrode was no longer detectable by XPS after 5 charging cycles. They attributed the loss of Ti 2p signal to instability due to participation in the redox reactions.…”
Section: Chemsuschemmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies such as surface coating, elemental doping and morphology control, are generally used to address the above issues. Directly coating on the interface is an effective way to suppress the interfacial reactions [23][24][25][26][27][28][29][30][31]. A number of approaches, such as spray pyrolysis [32], sol-gel method [33], and vapor deposition method [34], have been employed to inhibit the electrolyte decomposition.…”
Section: Introductionmentioning
confidence: 99%